Antimicrobial effect of commonly used herbs in Malaysia - Sarliza Yasmin, Sanusi (Pusat Pengajian Sains Perubatan, 2013)
The rhizome of Curcuma xanthorrhiza Roxb. (Zingiberaceae family, commonly known as temulawak) is a type of herb that has been used in therapeutics for hundreds of years. However, little attention has been paid to its effects on oral bacteria. The aims of this study were to determine the antimicrobial effects and the minimal inhibitory concentration (MIC) of Rhizoma Curcuma Xanthorrizae against oral bacteria. The former was determined using agar well diffusion method whereas the latter was determined using broth dilution (Tripticase Soy Broth) method. Nine types of oral bacteria namely Streptococcus mutans, Streptococcus sanguis, Streptococcus ora/is, Streptococcus sobrinus, Staphylococcus aureus, Lactobacillus Salivarius, Enterococcus faecalis, Pseudomonas aerugirosa and Eschericia coli were used in this study. Results showed that water extract of Rhizome Curcuma Xanthorrhizae did not exhibit any antibacterial effects against oral bacteria. Temulawak ethanol extract demonstrated antibacterial effects against Streptococcus mutans, Streptococcus sanguis, Streptococcus ora/is, Staphylococcus aureus and Enterococcus faecalis. The MIC value was lg/ml. The MIC value could be utilised as baseline data for contrivance of potential antimicrobial agents such as drugs or mouthwash. Further research should be carried out to deduce the active components of this plant that are responsible for its antibacterial activities.